Buyang Huanwu decoction affects gut microbiota and lipid metabolism in a ZDF rat model of co-morbid type 2 diabetes mellitus and obesity: An integrated metabolomics analysis - Liu, Mei; Zhao, Qinmian; Liu, Jiayan; Huang, Aijing; Xia, XinHua (Frontiers in Chemistry, 2022)
Type 2 diabetes (T2DM) is a chronic disease with many severe complications like blindness, amputation, renal failure, cardiovascular disease, etc. Currently, the prevention and treatment of T2DM is still a great important global challenge as the aging and the obese people increasing. Traditional Chinese medicine has the advantages of multi-target holistic and individual treatment in the intervention of obesity type 2 diabetes. However, most of those medicines from TCM to intervene in T2DM are not scientifically confirmed. Here, we choose a famous formula of TCM named with BuYangHuanWu Decoction (BYHWD) and sought to explore its scientific pharmacological activity on T2DM in modeled rats. First, we found that BYHWD exhibit excellent inhibitory actions against body fat accumulation, blood triglycerides increase, and blood glucose elevation induced by high fat diet in diabetic rats. Moreover, 16S rDNA sequencing of fecal samples identified the distinct community composition changes following BYHWD treatment, displayed as significantly increased Bacteroidetes as well as dramatically reduced Firmicutes in phyla level, and the remark increment genera of Lactobacillus and Blautia. Additionally, the lipid metabolomics based on liquid chromatography-mass spectrometry revealed a significant shift of lipid metabolites in liver after BYHWD treatment. Notably, these differential lipid metabolites were mainly involved in cholesterol metabolism, linoleic acid metabolism, glycerolipid metabolism, glycerophospholipid metabolism, insulin resistance, arachidonic acid metabolism, and alpha-linoleic acid metabolism, etc. Importantly, Spearman correlations analyses suggested that the disturbed gut microbiota and the altered lipid metabolites were associated with each other and also closely associated with the BYHWD’s bioactivities to reduce blood lipid and blood glucose, respectively. Collectively, these results suggest BYHWD could meliorate the gut microbiota dysbiosis and lipid metabolites alterations induced by high fat diet in diabetic rats, which not only provides a novel perspective on understanding the mechanisms of BYHWD’s bioactivity on T2DM, but also may be a possible way to use the advanced systems biology methods to reveal some unknown scientific laws in TCM theories.